PERBANDINGAN PELARUT ETANOL-AIR DALAM PROSES EKSTRAKSI DAUN BAWANG DAYAK (Eleutherine palmifolia Linn) TERHADAP AKTIVITAS ANTIOKSIDAN DENGAN METODE DPPH - Eka Kumalasari; Siska Musiam (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
The immune system can be damaged by the presence of free radicals. The formation of free radicals must be prevented by antioxidants. Humanes basically do not have antioxidant reserves in their her body, so that when there is exposure to excessive the radicals then the needs body antioxidant intake from the outside. At present it is encouraged the development of antioxidants derived from plants, which are relatively easier to obtain and safe for humans consumption. Potential to antioxidant plants one of them is dayak onion leaves. Dayak onion leaves are a typical plant Borneo Central used by the Dayak tribe as medicine. To get a high active ingredient in dayak onion leaves, it is necessary to optimize the type of maceration solvent. The types of solvents used are water and ethanol. Testing of antioxidant using activities DPPH (2,2-Diphenyl-1-picrylhydrazyl) as a free radical compound. The maximum wavelength of DPPH in this study is at 519 nm. The highest IC50 value was found on dayak onion leaf extract with water solvent which was 58.62 ppm, with ethanol-water solvent of 33.71 ppm, and the smallest with ethanol solvent of 26.98 ppm. Key: antioxydan, Eleutherine palmifolia of leave, DPPH